BUILDING EMOTIONAL REGULATION IN EARLY CHILDHOOD THROUGH CHARACTER-BASED HOLISTIC EDUCATION (PHBK) - Karissa, Violeta Chandra; Hayati, Nur (Ridwan Institute, 2024)
This article aims to analyze how the Holistic Character-Based Education (PHBK) model influences children's emotional regulation. This article uses Systematic Literature Review (SLR) to collect, analyze, and synthesize research results relevant to a certain topic in a systematic and structured manner. The results of the study show that the implementation of the PHBK learning model, through an integrated and holistic character approach, plays an important role in shaping emotional regulation in early childhood. The findings from this article can be used to inform educational practices by demonstrating how integrating character values into both formal and non-formal learning can enhance child emotional awareness and control. The research contributes to the understanding of character education's role in fostering emotional skills, a crucial aspect of child development.